2012
DOI: 10.1177/0363546512439180
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Proximal Tibial Slope on Dynamic Stability Testing of the Posterior Cruciate Ligament– and Posterolateral Corner–Deficient Knee

Abstract: These results suggest that increasing posterior tibial slope may improve sagittal stability in the PCL/PLC-deficient knee. Moreover, a knee with diminished posterior tibial slope may demonstrate greater multiplanar instability in this setting. Consequently, proximal tibial slope should be considered when treating combined PCL/PLC injuries of the knee.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
46
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(47 citation statements)
references
References 27 publications
1
46
0
Order By: Relevance
“…Giffin et al 16 showed that increasing the posterior tibial slope with an osteotomy resulted in a decrease in posterior tibial sag and translation by almost 50% at 90 degrees of knee flexion in cadavers with sectioned PCLs. Petrigliano et al 17 showed that decreasing the tibial slope with an osteotomy or making the slope more anterior (as seen in achondroplasts), resulted in a significantly increased posterior tibial translation and dynamic knee instability in patients with PCL and/or posterolateral corner injuries. We are unsure if the overall lower prevalence of PCL injuries compared with ACL injuries contributes to the lack of PCL injuries seen in our study, even though the achondroplasts' more anterior slope would possibly predispose them to these injuries.…”
Section: Discussionmentioning
confidence: 99%
“…Giffin et al 16 showed that increasing the posterior tibial slope with an osteotomy resulted in a decrease in posterior tibial sag and translation by almost 50% at 90 degrees of knee flexion in cadavers with sectioned PCLs. Petrigliano et al 17 showed that decreasing the tibial slope with an osteotomy or making the slope more anterior (as seen in achondroplasts), resulted in a significantly increased posterior tibial translation and dynamic knee instability in patients with PCL and/or posterolateral corner injuries. We are unsure if the overall lower prevalence of PCL injuries compared with ACL injuries contributes to the lack of PCL injuries seen in our study, even though the achondroplasts' more anterior slope would possibly predispose them to these injuries.…”
Section: Discussionmentioning
confidence: 99%
“…The posterior stability and the range of the knee are reduced consequently. [13] In addition, the HE of the knee due to the slope reduction increases the load of the anterior part of the tibial plateau, which might speed up osteoarthritis progression. What is more, the secondary deformity and osteoarthritis of the ankle could not be ignored in this patient and this can be explained by the compensatory mechanism of the gait.…”
Section: Discussionmentioning
confidence: 99%
“…High tibial osteotomy (HTO) is an alternative to total knee arthroplasty (TKA) that is routinely used to treat moderate osteoarthritis (OA) localized to one compartment of the knee, especially in young, active patients who meet the criteria for undergoing the procedure . With an HTO, the surgeon aims to change the coronal alignment of the leg in order to shift the center of force passing axially through the knee from the arthritic region of the knee towards the unaffected side …”
Section: Introductionmentioning
confidence: 99%